I-radicals and right perfect rings - Rump, W. (Український математичний журнал, 2007)
We determine the rings for which every hereditary torsion theory is an S-torsion theory in the sense of Komarnitskiy. We show that such rings admit a primary decomposition. Komarnitskiy obtained this result in the special case of left duo rings.